In Vitro Inhibitory Activity of Dayak Onion (Eleutherine bulbosa Mill.) Essential Oil Against Klebsiella pneumoniae - Marwan Hermawan; Amanah Amanah; Nurbaiti Nurbaiti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The cases of Klebsiella pneumoniae infec on in West Java province is s ll high. Klebsiella pneu- moniae bacterium can produce the Extended Spectrum Beta Lactamase enzyme leading to an bio cs resistant, so it is important to look for natural and inexpensive an bio c alterna ves; one of which is Dayak onion plant (Eleutherine bulbosa Mill). The content found in Dayak onion is believed to inhibit the growth of Klebsiella pneu- moniae bacteria. This study aims to determine the effec veness of Dayak onion essen al oil on the growth of Klebsiella pneumoniae bacteria. Methods: This study was an experimental study with a post-test control group design using the culture of Kleb- siella pneumoniae on the media Muller Hinton Agar in 7 groups. Groups 1 to 5 (K1 to K5) were given sequen ally Dayak Onion essen al oil solu on in 10% DMSO solvent with concentra ons of 50%, 25%, 12.5%, 6.25%, and 3.125%. Group 6 (K6) was posi ve control (+) with 5 μg Levofloxacin, and Group 7 (K7) was Nega ve (-) with 10% DMSO. The treatment results were measured by the diameter of the host zone and the collected data were analyzed using One-way ANOVA with appropriate Post hoc analysis. Results: The results showed that that there are differences in each group to inhibit the growth of bacteria (p <0.005). K1 are higher than K2, K3, K4, K5, and K7 with increasing concentra ons showed greater inhibi on. Levofloxacin (K6) showed the highest inhibitory power. Conclusion: The results showed that that there are differences in each group to inhibit the growth of bacteria (p <0.005). K1 are higher than K2, K3, K4, K5, and K7 with increasing concentra ons showed greater inhibi on. Levofloxacin (K6) showed the highest inhibitory power.